The role of autophagy in pancreatic diseases - Zhang, Wen-Gang; Wu, Qing-Zhen; Shao, Bo-Zong (Frontiers in Pharmacology, 2024)
Pancreatic diseases such as pancreatitis and pancreatic cancer represent significant health challenges characterized by high mortality rates and limited survival durations.Autophagy, a crucial cellular catabolic process, has emerged as a focal point in understanding various pathological conditions, spanning inflammation-related disorders to malignant neoplasms. This comprehensive review aims to elucidate the biological intricacies of autophagy and its pivotal roles within two extensively researched pancreatic diseases, namely pancreatitis and pancreatic cancer, drawing upon recent scholarly contributions. The discussion will delve into the nuanced mechanisms underlying autophagy's involvement in these diseases, shedding light on its potential as a therapeutic target. Furthermore, the review will explore cutting-edge therapeutic interventions leveraging autophagy regulation for managing pancreatitis and pancreatic cancer. Through this analysis, we endeavor to offer novel insights into the pathophysiology of pancreatic disorders and contribute to the development of innovative therapeutic modalities in this challenging clinical domain.